Identification of actin as a direct proteomic target of berberine using an affinity-based chemical probe and elucidation of its modulatory role in actin assembly. Issue 52 (15th June 2017) - Yi, Chae-Min; Yu, Jihyun; Kim, Hyunbin; Lee, Na-Rae; Kim, Sang Won; Lee, Noh-Jin; Lee, Jun; Seong, Jihye; Kim, Nam-Jung; Inn, Kyung-Soo
Abstract : Actin was identified as a direct target of berberine via a chemoproteomic approach and its assembly was modulated by berberine. Abstract : Despite the diverse pharmacological activities of berberine, including anti-cancer and anti-inflammatory effects, the direct proteomic targets of berberine have remained largely unknown. Here, we have identified actin as a direct proteomic target of berberine using an affinity-based chemical probe. In addition, we found that actin assembly was significantly modulated by berberine in vitro at the biochemical level and cellular level.